Study about the Manchester Triage System subtriage in patients that visited the Emergency Department due to headache - García-Azorín, D.; Abelaira-Freire, J.; Rodriguez-Adrada, E.; González-García, N.; Guerrero, Á.L.; Porta-Etessam, J.; Martín-Sánchez, F.J. (Neurología (Barcelona, English ed. ), 2023)
Headache is a frequent cause of consultation; it is important to detect patients with secondary headache, particularly high-risk secondary headache. Such systems as the Manchester Triage System (MTS) are used for this purpose. This study aims to evaluate the frequency of undertriage in patients attending the emergency department due to headache. We studied a series of consecutive patients who came to the emergency department with headache and presenting some warning sign, defined as the presence of signs leading the physician to request an emergency neuroimaging study and/or assessment by the on-call neurologist. The reference diagnosis was established by neurologists. We evaluated the MTS triage level assigned and the presence of warning signs that may imply a higher level than that assigned. We registered a total of 1120 emergency department visits due to headache, and 248 patients (22.8%) were eligible for study inclusion. Secondary headache was diagnosed in 126 cases (50.8% of the sample; 11.2% of the total), with 60 cases presenting high-risk secondary headache (24.2%; 5.4%). According to the MTS, 2 patients were classified as immediate (0.8%), 26 as very urgent (10.5%), 147 as urgent (59.3%), 68 as normal (27.4%), and 5 as not urgent (2%). The percentage of patients undertriaged was 85.1% in the very urgent classification level and 23.3% in the urgent level. During the study period, at least one in 10 patients attending the emergency department due to headache had secondary headache; one in 20 had high-risk secondary headache. The MTS undertriaged most patients with warning signs suggesting a potential emergency. La cefalea es un motivo de consulta urgente frecuente, siendo la prioridad detectar a pacientes con cefalea secundaria, especialmente cefaleas secundarias de alto riesgo (CESAR). Para ello, se emplean sistemas de triaje como el Sistema de Triaje de Manchester (STM). Pretendemos evaluar la frecuencia de subtriaje en pacientes que acudieron a urgencias por cefalea. Estudio de serie de casos consecutivos. Se analizaron pacientes que acudieron a urgencias refiriendo cefalea y tuvieron algún dato de alarma, definido como la presencia de datos que motivasen la solicitud de neuroimagen urgente y/o la valoración por neurología de guardia. El diagnóstico de referencia fue realizado por neurólogos. Se evaluó el nivel de triaje asignado por el STM y la presencia de datos de alarma que implicaría el triaje en un nivel superior al asignado. Hubo 1120 visitas a urgencias por cefalea, siendo elegibles 248 pacientes (22,8%). Se diagnosticó cefalea secundaria en 126 casos (50,8% de la muestra, 11,2% del total), siendo 60 CESAR (24,2% y 5,4%). El STM clasificó 2 pacientes como críticos (0,8%), 26 emergencias (10,5%), 147 urgencias (59,3%), 68 como estándar (27,4%) y 5 como no urgente (2%). El porcentaje de pacientes infratriados fue del 85,1% en el nivel “emergencia” y 23,3% en el de “urgencia”. Durante el periodo de estudio, al menos uno de cada diez pacientes que acudió a urgencias por cefalea tenía una cefalea secundaria y uno de cada veinte una CESAR. El STM infratrió a la mayoría de pacientes con datos que implicarían una potencial emergencia.